Psycological aspects of time and space perception in literal text - Oksana O. Kandrashkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
He article gives a brief outline of categories of time and space in philosophy, psychology and linguistics. It highlights the main properties of such categories in literal text. It also determines main differences and similarities between “real” time and space and their representation in literature.